Proteína C reactiva, síndrome metabólico y riesgo cardiovascular en la población costarricense nacida entre 1945 y 1955 - Aguilar Fernández, Eduardo (2020)
“C reactive protein, metabolic syndrome and cardiovascular risk in the Costa Rican population born between 1945 and 1955”. Introduction: Several studies have mentioned that there is a relationship between C reactive protein (CRP) and the metabolic syndrome (MS) and that this protein is a risk factor of cardiovascular disease. Objective: We studied the relationship of CRP with MS in the Costa Rican population. Methods: People born in Costa Rica between 1945 and 1955 and participants in CRELES-RC project were included in the study (n= 2 273). MS was adapted according to the American Heart Association and National Heart, Lung and Blood Institute definition. Results: The prevalence of MS increased with elevated CRP levels (p< 0,001) and was higher in women (p< 0,001). CRP was independently and positively associated to waist circumference and negatively associated to HDL-cholesterol. The strongest CRP determinant was waist circumference (PSup= 67,8). After adjustment for age, sex, residence area, smoking and alcohol, in the highest quartile of CRP levels (CRP> 4 mg/L), the risk for MS was higher compared with that in the lowest quartile of CRP levels. Cardiovascular risk was higher in people with high levels of CRP. Conclusions: CRP levels is associated with the MS among Costa Ricans born between 1945 and 1955.